Negative electrode active material, method for preparing negative electrode active material, negative electrode composition, negative electrode for lithium secondary battery comprising negative electrode composition, and lithium secondary battery comprising negative electrode

Preparing silicon-based active materials by chemical methods and forming a carbon coating on their surfaces solves the problem of disconnection of conductive paths caused by volume expansion of silicon-based active materials during charge and discharge, and suppresses gas generation during slurry preparation, achieving Improved battery performance and extended service life.

CN119343784APending Publication Date: 2025-01-21LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046116.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-31
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

When using silicon-based active material as the negative electrode active material, volume expansion during charging and discharging leads to disconnection of the conductive path, resulting in deterioration of battery performance, and when preparing the slurry, gas is generated due to the reaction of silicon and solvent, resulting in uneven electrode coating and Service life characteristics are deteriorated.

Method used

Silicon-based active materials are prepared through chemical methods, and a carbon coating with specific conditions is formed on the surface. The carbon coating serves as a protective layer to inhibit the reaction between silicon and solvent, prevent the generation of hydrogen, reduce the generation of bubbles, improve conductivity, and reduce the electrode temperature. resistance.

Benefits of technology

It achieves uniform reactions during lithium intercalation and deintercalation reactions, reduces the stress applied to silicon-based active materials, extends the service life of the electrode, and improves the energy density and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343784A_ABST
    Figure CN119343784A_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode active material, a method for preparing the negative electrode active material, a negative electrode composition, a negative electrode comprising the negative electrode composition, and a lithium secondary battery, the negative electrode active material comprising a silicon-based active material and a carbon coating layer surrounding at least a part of an outer surface of the silicon-based active material, wherein the carbon coating layer contains carbon having an ID / IG of 0.1 to 1.2 when measured by Raman spectroscopy, and the silicon-based active material contains a compound selected from the group consisting of SiOx (x = 0) and SiOx (0lt; xlt; 2), and the content of SiOx (x = 0) is 70 parts by weight or more based on 100 parts by weight of the silicon-based active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0110080 filed on August 31, 2022, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a negative electrode active material, a method for preparing the negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode composition, and a lithium secondary battery comprising the negative electrode. Background Art

[0003] Due to the rapid increase in the use of fossil fuels, there is an increasing demand for the use of alternative or clean energy, and as part of this trend, the most active research area is the field of power generation and storage using electrochemical reactions.

[0004] Currently, representative examples of electrochemical devices using such electrochemical energy include secondary batteries, and their use fields are increasingly expanding.

[0005] With the technological development and increased demand for mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, research on the preparation method of high-density electrodes with higher energy density per unit volume has been actively carried out.

[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and silicon-based particles having a high discharge capacity can be used as the negative electrode active material.

[0007] In particular, with the recent increase in demand for high-density energy batteries, methods of using silicon-based compounds such as Si / C or SiOx together to increase capacity have been actively studied. The capacity of the silicon-based compounds is as high as more than 10 times that of graphite-based materials as negative electrode active materials. Although the silicon-based compounds as high-capacity materials have higher capacity than the graphite used in the prior art, there is a problem that the volume expands rapidly during charging and disconnects the conductive path, resulting in deterioration of battery characteristics.

[0008] Therefore, in order to solve the problems when silicon-based compounds are used as negative electrode active materials, measures for adjusting the driving potential have been discussed; measures for suppressing the volume expansion itself, such as a method of further coating the active material layer with a thin film and a method of adjusting the particle size of the silicon-based compound; various measures for preventing the conductive path from being disconnected, etc., but since the performance of the battery may deteriorate instead, there are limitations in the application of the measures; there are limitations in the application of these methods, so that there are still limitations in the commercialization of the preparation of batteries having negative electrodes containing high content of silicon-based compounds.

[0009] In addition, although research has been conducted on reducing electrode resistance in electrodes using silicon-based compounds to ensure service life stability, there are still problems such as gas generation due to reaction with solvents when preparing a slurry containing silicon-based active materials, resulting in problems such as uneven electrode coating and deterioration of service life characteristics.

[0010] Therefore, research is required on silicon-based active materials themselves which can prevent the conductive path from being damaged due to volume expansion of silicon-based compounds and suppress gas generation when forming slurry even when the silicon-based active materials are used as negative electrode active materials for improving capacity characteristics.

[0011] [Related technical literature]

[0012] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention

[0013] Technical issues

[0014] When a silicon-based active material is prepared using a chemical processing method instead of the existing pulverization processing method, the physical properties of the silicon-based active material itself can be adjusted, thereby confirming that during the lithium insertion / deinsertion reaction, the reaction occurs uniformly and the stress applied to the silicon-based active material is reduced. However, even in this case, during the preparation of the slurry, the generation of gas due to the reaction between silicon and the slurry solvent becomes a problem, and it has been found that when a coating having a specific composition is formed on the silicon-based active material prepared as described above, these problems can be solved.

[0015] Therefore, the present application relates to a negative electrode active material capable of solving the above-mentioned problems, a method for preparing the negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery including the negative electrode composition, and a lithium secondary battery including the negative electrode.

[0016] Technical Solution

[0017] One exemplary embodiment of the present specification provides a negative electrode active material, which includes: a silicon-based active material; and a carbon coating that surrounds at least a part of the outer surface of the silicon-based active material. When measured by Raman spectroscopy, the carbon coating contains carbon with an ID / IG of 0.1 to 1.2. The silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and the content of SiOx (x = 0) is 70 parts by weight or more based on 100 parts by weight of the silicon-based active material.

[0018] Another exemplary embodiment provides a method for preparing a negative electrode active material, which includes: depositing a silicon-based active material on a substrate by a chemical reaction of a silane gas; obtaining the silicon-based active material deposited on the substrate; and forming a carbon coating on at least a part of the outer surface of the silicon-based active material.

[0019] Yet another exemplary embodiment aims to provide a negative electrode composition, which includes: the negative electrode active material according to the present application; a negative electrode conductive material; and a negative electrode binder.

[0020] Yet another exemplary embodiment aims to provide a negative electrode for a lithium secondary battery, which includes: a negative electrode current collector layer; and a negative electrode active material layer disposed on one or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer includes the negative electrode composition according to the present application or a cured product thereof.

[0021] Finally, a lithium secondary battery is provided, which includes: a positive electrode; the negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

[0022] Advantageous Effects

[0023] The negative electrode active material of the present invention includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2) as the silicon-based active material, and includes 70 parts by weight or more of SiOx (x = 0) based on 100 parts by weight of the silicon-based active material, that is, has a pure Si active material. At the same time, different from the existing pulverization processing method, it is prepared by controlling the reaction conditions of a chemical method. Therefore, the negative electrode active material of the present invention includes a silicon-based active material that satisfies predetermined physical properties. When using the silicon-based active material prepared as described above, during charge and discharge, the reaction can be carried out uniformly during the lithium insertion and extraction reactions, and the stress applied to the silicon-based active material can be reduced to alleviate particle breakage, thereby improving the service life retention rate of the electrode.

[0024] In addition, the present application is characterized in that a carbon coating of specific conditions is formed on at least a portion of the outer surface of the silicon-based active material prepared as described above. Therefore, the present application has the following characteristics: the carbon coating acts as a protective layer to prevent hydrogen generation reaction by inhibiting the reaction between the surface of the silicon-based active material and the solvent during slurry formation, thereby being able to reduce uneven electrode coating caused by the generation of bubbles during electrode coating.

[0025] In addition, the present application has the following features: since the conductivity of the above-mentioned carbon coating is higher than a predetermined range, the resistance of the negative electrode active material itself is reduced, and thus, the electrode resistance is reduced due to the improved conductivity, thereby improving the service life stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a diagram showing a stack structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.

[0027] Figure 2 is a diagram illustrating a stack structure of a lithium secondary battery according to an exemplary embodiment of the present application.

[0028] Figure 3 It is a diagram showing a method of calculating the grain size.

[0029] <Description of Reference Numerals and Symbols>

[0030] 10: Negative electrode collector layer

[0031] 20: Negative electrode active material layer

[0032] 30: Diaphragm

[0033] 40: Positive electrode active material layer

[0034] 50: Positive electrode collector layer

[0035] 100: Negative electrode for lithium secondary battery

[0036] 200: Positive electrode for lithium secondary battery DETAILED DESCRIPTION

[0037] Before describing the present invention, some terms will first be defined.

[0038] In the present specification, when a part “comprises” a constituent element, unless otherwise particularly described, this does not mean that other constituent elements are excluded but means that other constituent elements may further be included.

[0039] In this specification, “p to q” means a range of “p or more and q or less”.

[0040] In this specification, the "specific surface area" is measured by the BET method, and specifically is calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77 K) using BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the measurement method.

[0041] In this specification, "Dn" means particle size distribution, and means the particle size at n% point according to the cumulative distribution of the number of particles of particle size. That is, D50 is the particle size (average particle size) at 50% point according to the cumulative distribution of the number of particles of particle size, D90 is the particle size at 90% point according to the cumulative distribution of the number of particles of particle size, and D10 is the particle size at 10% point according to the cumulative distribution of the number of particles of particle size. On the other hand, the average particle size can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in the diffraction pattern according to the particle size when the particle passes through the laser beam, thereby calculating the particle size distribution.

[0042] In an exemplary embodiment of the present application, the particle size or particle diameter may mean an average diameter or a representative diameter of each particle forming the metal powder.

[0043] In the present specification, the fact that a polymer contains a monomer as a monomer unit means that the monomer participates in a polymerization reaction, thereby being contained as a repeating unit in the polymer. In the present specification, when a polymer contains a monomer, it is interpreted as the same as when the polymer contains a monomer as a monomer unit.

[0044] In this specification, "polymer" is understood to be used in a broad sense including copolymers unless it is otherwise specified as a "homopolymer".

[0045] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene conversion molecular weights measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specified, molecular weight means weight average molecular weight.

[0046] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art to which the present invention pertains can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.

[0047] In an exemplary embodiment of the present specification, a negative electrode active material is provided, the negative electrode active material comprising: a silicon-based active material; and a carbon coating surrounding at least a part of the outer surface of the silicon-based active material, wherein when measured using Raman spectroscopy, the carbon coating comprises carbon with an ID / IG of 0.1 to 1.2, the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and the content of SiOx (x = 0) is 70 parts by weight or more based on 100 parts by weight of the silicon-based active material.

[0048] The negative electrode active material according to the present application comprises a carbon coating surrounding at least a part of the surface of the silicon-based active material (prepared by a specific preparation method). Therefore, the negative electrode active material according to the present application has the following characteristics: the carbon coating serves as a protective layer, preventing the hydrogen generation reaction by suppressing the reaction between the surface of the silicon-based active material and the solvent during slurry formation, thereby being able to reduce uneven electrode coating caused by the generation of bubbles during electrode coating.

[0049] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the carbon coating has a thickness of 1 nm or more and 10 μm or less.

[0050] In another exemplary embodiment, the carbon coating may have a thickness of 1 nm or more and 10 μm or less, preferably 10 nm or more and 0.1 μm or less, more preferably 15 nm or more and 0.05 μm or less.

[0051] When the thickness of the carbon coating satisfies the above range, it is possible to easily prevent the contact between the solvent and the silicon-based active material, and by having the above thickness range, the conductivity can also be improved, and the content of the silicon-based active material can also be maximized, such that the negative electrode active material has excellent capacity characteristics.

[0052] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the carbon coating has a conductivity of 100 mS / m or more and 1000 mS / m or less.

[0053] In the present application, the conductivity refers to the ability of the material itself to conduct current when an electric field is applied, and can be used as a parameter representing the degree of good flow of current within the material.

[0054] The conductivity can be measured using common measurement methods used in the art, and the reciprocal of the conductivity can mean resistivity, and the resistivity can have different values depending on the type and composition of the material.

[0055] In an exemplary embodiment of the present application, the carbon coating layer may have an electrical conductivity of 100 mS / m or more and 1000 mS / m or less, preferably 120 mS / m or more and 900 mS / m or less, and more preferably 180 mS / m or more and 800 mS / m or less.

[0056] The carbon coating according to the present application inhibits the reaction between the silicon-based active material and the slurry solvent as described above, and at the same time has high electrical conductivity as described above, and since the carbon coating can be formed on the surface of the silicon-based active material to reduce the resistance of the negative electrode active material, the carbon coating according to the present application has the following characteristics: it can reduce the resistance of the electrode due to the increase in the conductivity of the active material, thereby improving the service life stability.

[0057] In an exemplary embodiment of the present application, there is provided a negative electrode active material, wherein an arrangement area of ​​the carbon coating layer is 90% or more based on an outer surface of the silicon-based active material.

[0058] The arrangement area may mean the extent to which the carbon coating layer is coated on the outer surface of the silicon-based active material. That is, when the carbon coating layer completely surrounds the silicon-based active material, the arrangement area may be 100%, which may mean that the surface of the silicon-based active material can be isolated from the outside, that is, isolated by the carbon coating layer.

[0059] In an exemplary embodiment of the present application, based on the outer surface of the silicon-based active material, the layout area of ​​the carbon coating can be greater than 90%, greater than 91%, or greater than 92%, and based on the outer surface area of ​​the silicon-based active material, it can satisfy the range of less than 100%, less than 99%, or less than 95%.

[0060] By having the arrangement area of ​​the carbon coating as described above, gas generation can be more easily suppressed, and when included in an electrode in the future, the carbon coating has a feature that can promote the function as a silicon-based active material. In particular, the carbon coating according to the present application is used to obtain the effect of suppressing gas generation, and when the arrangement area of ​​the carbon coating is 100%, the carbon coating according to the present application can block contact with water in a slurry state, and thus has a feature that can reduce gas generation.

[0061] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the carbon coating layer includes one or more selected from the group consisting of crystalline carbon and amorphous carbon.

[0062] In an exemplary embodiment of the present application, the carbon coating layer includes crystalline carbon.

[0063] In an exemplary embodiment of the present application, the carbon coating comprises amorphous carbon.

[0064] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein when measured by Raman spectroscopy, the carbon coating comprises carbon with an ID / IG of 0.1 to 1.2.

[0065] In another exemplary embodiment, the ID / IG may satisfy the range of 0.1 to 1.2, preferably 0.13 to 1.2.

[0066] The ID / IG may refer to an index for confirming defects in the carbon structure and may refer to an index for measuring the degree of defects in the carbon material by Raman spectroscopy measurement.

[0067] By including carbon that satisfies the Raman spectroscopy range as described above, the battery has the characteristic that the service life performance is excellent during subsequent battery driving.

[0068] In an exemplary embodiment of the present application, the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, 70 parts by weight or more of the SiOx (x = 0) may be included.

[0069] In an exemplary embodiment of the present application, the silicon-based active material comprises SiOx (x = 0), and based on 100 parts by weight of the silicon-based active material, 70 parts by weight or more of the SiOx (x = 0) may be included.

[0070] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of the SiOx (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and the content may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.

[0071] In an exemplary embodiment of the present application, the silicon-based active material particularly comprising pure silicon (Si) particles may be used as the silicon-based active material. Using pure silicon (Si) particles as the silicon-based active material may mean that, based on all 100 parts by weight of the silicon-based active material as described above, the content of pure Si particles (SiOx(x = 0)) not combined with other particles or elements is within the above range.

[0072] In an exemplary embodiment of the present application, based on 100 parts by weight of the silicon-based active material, the silicon-based active material may be composed of silicon-based particles having 100 parts by weight of SiOx (x = 0).

[0073] In an exemplary embodiment of the present application, the silicon-based active material may contain metal impurities, in which case the impurities are metals that may be generally contained in the silicon-based active material, and specifically, the content may be 0.1 parts by weight or less based on 100 parts by weight of the silicon-based active material.

[0074] Since the silicon-based active material has a significantly higher capacity than the graphite-based active material used in the related art, attempts to apply the silicon-based active material are increasing, but since the silicon-based active material has a high volume expansion rate during the charge and discharge process, the attempts are limited to the case where a small amount of the silicon-based active material is mixed with the graphite-based active material and used.

[0075] Therefore, the present invention solves the above-mentioned problems by adjusting the grain size or specific surface area of ​​the silicon-based active material itself instead of adjusting the composition of the conductive material and the binder while only using the silicon-based active material as the negative electrode active material to improve the capacity performance.

[0076] In an exemplary embodiment of the present application, the silicon-based active material may have a grain size of 200 nm or less.

[0077] In another exemplary embodiment, the silicon-based active material may have a grain size of 200 nm or less, preferably 130 nm or less, more preferably 110 nm or less, even more preferably 100 nm or less, specifically 95 nm or less, more specifically 91 nm or less. The silicon-based active material may have a grain size range of 10 nm or more, preferably 15 nm or more.

[0078] The silicon-based active material has the above-mentioned grain size, and the grain size of the silicon-based active material can be adjusted by changing the process conditions during the preparation process. In this case, by satisfying the above-mentioned range, the grain boundaries are widely distributed, so that during the embedding of lithium ions, lithium ions can enter uniformly, which can reduce the stress applied when lithium ions are embedded in silicon particles, thereby alleviating the rupture of particles. As a result, the silicon-based active material has the characteristic of being able to improve the service life stability of the negative electrode. When the grain size exceeds the above-mentioned range, the grain boundaries in the particles are narrowly distributed. In this case, lithium ions are unevenly embedded in the particles, so that the stress caused by ion embedding is large, and thus particle rupture occurs.

[0079] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon-based active material includes a crystal structure having a grain distribution of 1 nm or more and 200 nm or less, and an area ratio of the crystal structure is 5% or less based on the total area of ​​the silicon-based active material.

[0080] In another exemplary embodiment, the area ratio of the crystal structure may be 5% or less or 3% or less, and may be 0.1% or more based on the total area of ​​the silicon-based active material.

[0081] That is, the silicon-based active material according to the present application has a grain size of 200 nm or less, and the size of each crystal structure is small, which can satisfy the above area ratio. Therefore, the distribution of grain boundaries can be widened, thereby achieving the above effect.

[0082] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the number of crystal structures included in the silicon-based active material is 20 or more.

[0083] In another exemplary embodiment, the number of crystal structures included in the silicon-based active material may be 20 or more, 30 or more, or 35 or more, and may satisfy a range of 60 or less, or 50 or less.

[0084] That is, as described above, when the grain size satisfies the above range and the number of crystal structures also satisfies the above range, the strength of the silicon-based active material itself has an appropriate range, so that the silicon-based active material has the characteristic of being able to impart flexibility when contained in an electrode, and also has the characteristic of being able to effectively suppress volume expansion.

[0085] In the present application, the crystal grain means a crystal particle in a metal or material, which is a collection of irregular shapes of microscopic size, and the grain size may mean the diameter of the observed crystal grain particles. That is, in the present application, the grain size means the size of a domain that shares the same crystal orientation in a particle, and has a different concept from the grain size or particle diameter size that represents the material size.

[0086] In an exemplary embodiment of the present application, the grain size can be calculated as a full width at half maximum (FWHM) value by XRD analysis. Specifically, Figure 3 The method for calculating the grain size is shown in Figure 3 In the above, the remaining values ​​except L are measured by XRD analysis of the silicon-based active material, and the grain size can be measured by the Debey-Scherrer formula indicating that FWHM is inversely proportional to the grain size. In this case, the Debey-Scherrer formula is the same as the following formula 1-1.

[0087] [Formula 1-1]

[0088] FWHM=Kλ / LCosθ

[0089] In formula 1-1,

[0090] L is the grain size, K is a constant, θ is the Bragg angle, and λ refers to the wavelength of the X-ray.

[0091] Furthermore, the shapes of the grains are various and thus can be measured in three dimensions. Generally, the grain size can be measured by a generally used circle method and a diameter measurement method, but the present invention is not limited thereto.

[0092] The diameter measurement method can be performed by drawing 5 to 10 equilibrium lines each having a length of L mm on a micrograph of the particle to be measured, counting the number of grains z on the line, and averaging the number of grains z. In this case, only those grains that enter completely are counted, while those that cross the line are excluded. When the number of lines is defined as P and the magnification is defined as V, the average particle diameter can be calculated using the following formula 1-2.

[0093] [Formula 1-2]

[0094] Dm=(L*P*10 3 ) / (zV) (μm)

[0095] In addition, in the circle method, the average particle area can be calculated using the following formula 1-3 by the following method: after drawing a circle with a predetermined diameter on a micrograph of the target particle, the average area of ​​the grains is obtained using the number of grains entering the circle and the number of grains on the boundary line.

[0096] [Formula 1-3]

[0097] Fm=(Fk*10 6 ) / ((0.67n+z)V 2 ) (μm 2 )

[0098] In Formula 1-3, Fm means the average particle area, Fk means the measurement area on the photograph, z means the number of particles entering the circle, n means the number of particles on the arc, and V means the magnification of the microscope.

[0099] In an exemplary embodiment of the present application, the negative electrode active material may include a 2 Silicon-based active materials having a specific surface area of ​​more than 1000 μm.

[0100] In another exemplary embodiment, the silicon-based active material may have a thickness of 0.25 m 2 / g or more, preferably 0.28 m 2 / g or more, more preferably 0.30 m 2 / g or more, specifically 0.31 m 2 / g or more, more specifically 0.32 m 2 / g or more. The specific surface area of ​​the silicon-based active material may satisfy 3 m 2 / g or less, preferably 2.5 m 2 / g or less, more preferably 2.2 m 2 The specific surface area can be measured according to DIN 66131 (using nitrogen).

[0101] The silicon-based active material has the above-mentioned specific surface area, and the specific surface area of ​​the silicon-based active material can be adjusted by changing the process conditions in the preparation process described below and the growth conditions of the silicon-based active material. That is, when the negative electrode active material is prepared using the preparation method according to the present application, the negative electrode active material has a larger specific surface area than particles with the same particle size due to the rough surface, and in this case, due to the increase in the bonding strength with the binder by satisfying the above range, the negative electrode active material has the characteristic of being able to reduce cracks in the electrode caused by repeated charge and discharge cycles.

[0102] In addition, during the insertion of lithium ions, lithium ions can enter uniformly, which can reduce the stress applied when lithium ions are inserted into silicon particles, thereby alleviating the breakage of particles. As a result, the negative electrode has a feature that can improve the service life stability of the negative electrode. When the specific surface area size is smaller than the above range, the surface is smoothly formed even when the particles have the same particle size, the bonding strength with the binder is deteriorated, and electrode cracks occur, and in this case, lithium ions are unevenly inserted into the particles, so that the particles break due to the large stress caused by the insertion of ions.

[0103] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon-based active material satisfies the range of the following formula 2-1.

[0104] [Formula 2-1]

[0105] X1 / Y1≤0.960

[0106] In formula 2-1,

[0107] X1 is the actual area of ​​the silicon-based active material, and

[0108] Y1 means the area of ​​a spherical particle having the same circumference as the silicon-based active material.

[0109] The measurement of formula 2-1 can be performed using a particle image analyzer. Specifically, after the silicon-based active material according to the present application is spread on a glass plate by air jet, a shadow image of the spread silicon-based active material particles can be taken to determine the shape of 10,000 silicon-based active material particles in the photograph. In this case, formula 2-1 is a value representing the average value of 10,000 particles. Formula 2-1 according to the present application can be measured by the above image, and the above formula 2-1 can be represented by the roundness of the silicon-based active material. The roundness can also be expressed by the formula [4π*actual area of ​​the silicon-based active material / (boundary) 2 ] to indicate.

[0110] In an exemplary embodiment of the present application, the circularity of the silicon-based active material may be, for example, 0.960 or less, for example, 0.957 or less. The circularity of the silicon-based active material may be 0.8 or more, for example, 0.9 or more, specifically 0.93 or more, more specifically 0.94 or more, and for example, 0.941 or more.

[0111] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon-based active material satisfies the range of the following formula 2-2.

[0112] [Formula 2-2]

[0113] X2 / Y2≤0.995

[0114] In formula 2-2,

[0115] Y2 is the actual circumference of the silicon-based active material, and

[0116] X2 is the perimeter of the circumscribed pattern of the silicon-based active material.

[0117] The measurement of formula 2-2 can be performed using a particle image analyzer. Specifically, after the silicon-based active material according to the present application is spread on a glass plate by air jet, a shadow image of the spread silicon-based active material particles can be taken to determine the shape of 10,000 silicon-based active material particles in the photograph. In this case, formula 2-2 is a value representing the average value of 10,000 particles. Formula 2-2 according to the present application can be measured by the above image, and the above formula 2-2 can be represented by the convexity of the silicon-based active material.

[0118] In an exemplary embodiment of the present application, X2 and Y2 may satisfy the range of X2 / Y2≤0.996, preferably the range of X2 / Y2≤0.995, and X2 and Y2 may satisfy the range of 0.8≤X2 / Y2, preferably 0.9≤X2 / Y2, more preferably 0.95≤X2 / Y2, and specifically 0.98≤X2 / Y2.

[0119] It can be meant that the smaller the value of the above formula 2-1 or 2-2, the greater the roughness of the silicon-based active material may be. When the silicon-based active material having the above range is used, the bonding strength between the silicon-based active material and the binder is increased, thereby having the characteristic of being able to reduce cracks in the electrode caused by repeated charge and discharge cycles.

[0120] In an exemplary embodiment of the present application, the silicon-based active material may include silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less.

[0121] The fact that the silicon-based active material contains silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less means that a large number of individual silicon-based particles having a particle size within the above range are contained, and the number of silicon-based particles contained is not limited.

[0122] When the silicon-based particles have a spherical shape, the particle size of the silicon-based particles can be expressed as the diameter of the silicon-based particles, but even in other non-spherical cases, the particle size can be measured by comparison with the spherical case. Generally, the particle size of individual silicon-based particles can be measured by measurement methods in the art.

[0123] On the other hand, the silicon-based active material of the present invention may have an average particle size (D50 particle size) of 3 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is included in the above range, since the specific surface area of ​​the particles is included in a suitable range, the viscosity of the negative electrode slurry is formed in a suitable range. Therefore, the dispersion of the particles constituting the negative electrode slurry is promoted. In addition, the size of the silicon-based active material has a value equal to or greater than the lower limit range, and since the composite composed of the conductive material and the binder in the negative electrode slurry makes the contact area between the silicon particles and the conductive material excellent, the possibility of the conductive network continuing increases, thereby improving the capacity retention rate. On the other hand, when the average particle size satisfies the above range, excessively large silicon particles are eliminated to form a smooth negative electrode surface, and therefore, the phenomenon of uneven current density during charge and discharge can be prevented.

[0124] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of ​​the silicon-based active material is preferably 0.01 m2 / g to 150.0 m 2 / g, more preferably 0.1m 2 / g to 100.0 m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, most preferably 0.2 m 2 / g to 18.0 m 2 The BET specific surface area is measured by DIN 66131 (using nitrogen).

[0125] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively but less preferably, the silicon particles may also have a fibrous structure, or be present in the form of a film or coating containing silicon.

[0126] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical form, and a roundness thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, and for example, 0.85 to 0.9.

[0127] In the present application, the circularity is determined by the following formula 3-1, where A is the area and P is the boundary line.

[0128] [Formula 3-1]

[0129] 4πA / P 2

[0130] In an exemplary embodiment of the present application, a negative electrode composition is provided, the negative electrode composition including: the negative electrode active material; a negative electrode conductive material; and a negative electrode binder.

[0131] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode active material is present in an amount of 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.

[0132] In another exemplary embodiment, the content of the negative electrode active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, based on 100 parts by weight of the negative electrode composition, and the content may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less.

[0133] The negative electrode composition according to the present application has the following characteristics: even if a negative electrode active material with a significantly high capacity is used within the above range, by using a negative electrode active material that satisfies a specific grain size and can suppress the volume expansion rate during charge and discharge, the performance of the negative electrode will not deteriorate even if the above range is included, and the output characteristics during charge and discharge are excellent.

[0134] In the prior art, it is common to use only graphite compounds as the negative electrode active material, but recently, as the demand for high-capacity batteries increases, attempts to mix and use silicon-based active materials have increased in order to increase capacity. However, in the case of the silicon-based active material, even if the characteristics of the silicon-based active material itself are adjusted as described above, the volume expands rapidly during charge and discharge, so that in some cases, the problem of damage to the conductive path formed in the negative electrode active material layer may occur.

[0135] Therefore, in an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a planar conductive material, and a linear conductive material.

[0136] In an exemplary embodiment of the present application, the dot-shaped conductive material can be used to enhance the conductivity of the negative electrode, and means a dot-shaped or spherical conductive material having conductivity without causing chemical changes. Specifically, the dot-shaped conductive material can be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and in terms of achieving high conductivity and excellent dispersibility, carbon black can be preferably included.

[0137] In an exemplary embodiment of the present application, the dot-shaped conductive material may have a diameter of 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g and above 60 m 2 / g or less BET specific surface area.

[0138] In an exemplary embodiment of the present application, the functional group content (volatile matter) of the dot-shaped conductive material may satisfy 0.01% to 1%, preferably 0.01% to 0.3%, and more preferably 0.01% to 0.1%.

[0139] In particular, when the functional group content of the dot-shaped conductive material satisfies the above range, there are functional groups located on the surface of the dot-shaped conductive material, so that when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, in the present invention, since a specific silicon-based active material is used, the functional group content of the dot-shaped conductive material can be reduced, and therefore, the present invention has an excellent effect in improving dispersibility.

[0140] In an exemplary embodiment of the present application, it is characterized in that the dot-shaped conductive material having a functional group content within the above range is included together with the silicon-based active material, and the functional group content can be adjusted according to the degree to which the dot-shaped conductive material is heat-treated.

[0141] In an exemplary embodiment of the present application, the dot-shaped conductive material may have a particle size of 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.

[0142] In an exemplary embodiment of the present application, the conductive material may include a planar conductive material.

[0143] The planar conductive material can be used to improve conductivity by increasing surface contact between silicon particles in the negative electrode while suppressing disconnection of the conductive path due to volume expansion. The planar conductive material can be in the form of a plate-like conductive material or a bulk conductive material.

[0144] In an exemplary embodiment of the present application, the planar conductive material may include at least one selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.

[0145] In an exemplary embodiment of the present application, the planar conductive material may have an average particle size (D50) of 2 μm to 7 μm, specifically 3 μm to 6 μm, more specifically 3.5 μm to 5 μm. When the average particle size satisfies the above range, sufficient particle size promotes dispersion without causing excessive increase in viscosity of the negative electrode slurry. Therefore, when the particles are dispersed using the same equipment and time, the dispersion effect is excellent.

[0146] In an exemplary embodiment of the present application, a negative electrode composition is provided in which the planar conductive material has D10 of 0.5 μm or more and 2.0 μm or less, D50 of 2.5 μm or more and 3.5 μm or less, and D90 of 6.5 μm or more and 15.0 μm or less.

[0147] In an exemplary embodiment of the present application, as the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area; or a low specific surface area planar conductive material may be used.

[0148] In an exemplary embodiment of the present application, as the planar conductive material, a planar conductive material with a high specific surface area; or a planar conductive material with a low specific surface area can be used without restriction, but in particular, the planar conductive material according to the present application may be affected to a certain extent by the dispersion effect on the electrode performance, so it may be particularly desirable to use a planar conductive material with a low specific surface area that does not cause dispersion problems.

[0149] In an exemplary embodiment of the present application, the planar conductive material may have a size of 1 m 2 / g or more BET specific surface area.

[0150] In another exemplary embodiment, the planar conductive material may have a size of 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m 2 / g or less BET specific surface area.

[0151] As the planar conductive material according to the present application, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used.

[0152] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 300 m 2 / g or less.

[0153] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g or more and 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.

[0154] As other conductive materials, there may be linear conductive materials such as carbon nanotubes. Carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" used herein refers to a secondary shape in the form of a bundle or rope, in which a plurality of carbon nanotube units are arranged side by side or wound in an orientation such that the longitudinal axes of the carbon nanotube units are substantially the same. In the carbon nanotube unit, the graphite sheet has a cylindrical shape with a nanometer-sized diameter and has an sp2 bond structure. In this case, depending on the angle and structure of the curling of the graphite sheet, the carbon nanotube unit may exhibit the characteristics of a conductor or a semiconductor. Compared with entangled type carbon nanotubes, the bundle-type carbon nanotubes may be uniformly dispersed during the preparation of the negative electrode, and the conductivity of the negative electrode may be improved by smoothly forming a conductive network in the negative electrode.

[0155] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the content of the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode composition.

[0156] In another exemplary embodiment, the content of the negative electrode conductive material may be 0.1 parts by weight or more and 40 parts by weight or less, preferably 0.2 parts by weight or more and 30 parts by weight or less, more preferably 0.4 parts by weight or more and 25 parts by weight or less, and most preferably 0.4 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the negative electrode composition.

[0157] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode conductive material comprises a planar conductive material; and a linear conductive material.

[0158] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode conductive material comprises the planar conductive material and the linear conductive material in an amount of 80 parts by weight or more and 99.9 parts by weight or less and 0.1 parts by weight or more and 20 parts by weight or less, respectively, based on 100 parts by weight of the negative electrode conductive material.

[0159] In another exemplary embodiment, the negative electrode conductive material may include the planar conductive material in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 85 parts by weight or more and 99.9 parts by weight or less, and more preferably 95 parts by weight or more and 98 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.

[0160] In yet another exemplary embodiment, the negative electrode conductive material may include the linear conductive material in an amount of 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.1 parts by weight or more and 15 parts by weight or less, and more preferably 0.2 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.

[0161] In an exemplary embodiment of the present application, since the negative electrode conductive material includes a planar conductive material and a linear conductive material, and the planar conductive material and the linear conductive material each satisfy the composition and proportion, the negative electrode conductive material has the following characteristics: it does not significantly affect the service life characteristics of existing lithium secondary batteries, and in particular, when it includes a planar conductive material and a linear conductive material, the sites at which the battery can be charged and discharged are increased, so the output characteristics at a high C rate are excellent and the amount of high-temperature gas generated is reduced.

[0162] In an exemplary embodiment of the present application, the negative electrode conductive material may be composed of a linear conductive material.

[0163] In particular, when the linear conductive material is used alone, the electrode tortuosity, which is a problem of the silicon-based negative electrode, can be simplified, thereby improving the electrode structure. Therefore, the negative electrode conductive material has a feature of being able to reduce the movement resistance of lithium ions in the electrode.

[0164] In an exemplary embodiment of the present application, when the negative electrode conductive material contains only the linear conductive material, the content of the negative electrode conductive material may be 0.1 parts by weight or more and 5 parts by weight or less, preferably 0.2 parts by weight or more and 3 parts by weight or less, and more preferably 0.4 parts by weight or more and 1 part by weight or less, based on 100 parts by weight of the negative electrode composition.

[0165] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material used for the positive electrode. That is, the negative electrode conductive material according to the present application is used to capture the contact sites between the silicon-based active materials in which the electrode volume expands greatly due to charge and discharge, while the positive electrode conductive material is used to play a buffering role as a buffer during rolling and to impart a part of conductivity, and its structure and function are completely different from those of the negative electrode conductive material of the present invention.

[0166] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material and has a completely different structure from the conductive material applied to a graphite-based active material. That is, the conductive material used for an electrode having a graphite-based active material simply has particles smaller than the active material, and thus has the characteristics of enhancing output characteristics and imparting a portion of conductivity, and its structure and function are completely different from the structure and function of the negative electrode conductive material applied together with the silicon-based active material in the present invention.

[0167] In an exemplary embodiment of the present application, the planar conductive material used as the above-mentioned negative electrode conductive material has a structure and function different from the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and means a material processed into a spherical or dot shape and used to promote the storage and release of lithium ions.

[0168] In contrast, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the plate-like conductive material is a material contained in order to maintain a conductive path in the negative electrode active material layer, and means a material for ensuring a conductive path in a planar shape in the negative electrode active material layer, rather than playing a role in storing and releasing lithium.

[0169] That is, in the present application, the fact that plate-like graphite is used as a conductive material means that the plate-like graphite is processed into a planar or plate-like shape and used as a material for ensuring a conductive path, rather than playing a role in storing or releasing lithium. In this case, the negative electrode active material contained together has a high capacity characteristic for lithium storage and release, and plays a role capable of storing and releasing all lithium ions transferred from the positive electrode.

[0170] In contrast, in the present application, the fact that a carbon-based active material is used as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.

[0171] That is, in one exemplary embodiment of the present application, artificial graphite or natural graphite as a carbon-based active material is in a dot-like form, and its BET specific surface area may satisfy 0.1 m 2 / g and above 4.5 m 2 / g or less. In addition, the plate-like graphite as a planar conductive material is in a planar form and may have a surface area of ​​5 m 2 / g or more BET specific surface area.

[0172] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid and materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0173] The negative electrode binder according to an exemplary embodiment of the present application plays a role in supporting the active material and the conductive material during the volume expansion and relaxation of the silicon-based active material, thereby preventing the distortion and structural deformation of the negative electrode structure. When the above-mentioned effects are met, all common binders can be applied, specifically, aqueous binders can be used, and more specifically, PAM-based binders can be used.

[0174] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may be 5 parts by weight or more and 10 parts by weight or more, based on 100 parts by weight of the negative electrode composition.

[0175] Another exemplary embodiment of the present application provides a method for preparing the negative electrode active material according to the present application, the method comprising: depositing a silicon-based active material onto a substrate by chemically reacting silane gas; obtaining the silicon-based active material deposited on the substrate; and forming a carbon coating on at least a portion of the outer surface of the silicon-based active material.

[0176] According to one example, the silane gas may include one or more gases selected from monosilane, dichlorosilane, and trichlorosilane, and may specifically be trichlorosilane gas.

[0177] In the present application, a method for preparing a negative electrode active material is provided, wherein the deposition of the silicon-based active material onto a substrate by chemically reacting silane gas is performed under a high temperature condition of 100° C. or above.

[0178] In an exemplary embodiment of the present application, the deposition of the silicon-based active material onto the substrate by chemically reacting the silane gas can be performed under a pressure condition of 10 Pa to 150 Pa. The low pressure as described above can reduce the silicon growth rate, thereby achieving the formation of small grains. The step can be performed under a temperature condition of 100°C or more, specifically 500°C or more, preferably 800°C or more, more preferably 800°C to 1300°C, or 800°C to 1100°C. This is lower than the temperature in the existing gas atomization method of heating Si to more than 1600°C to melt silicon.

[0179] In an exemplary embodiment of the present application, the method may further include growing the silicon-based active material by crystal nucleation, and the growth of the silicon-based active material by crystal nucleation may be performed at a temperature of 800°C or above, preferably 800°C to 1300°C. This is lower than the temperature in the existing gas atomization method of heating Si to above 1600°C to melt silicon. In addition, the growth of the silicon-based active material by crystal nucleation may be performed at a pressure of 100 Pa to 150 Pa. The low pressure as described above can reduce the silicon growth rate, thereby achieving the formation of small grains and a specific specific surface area.

[0180] In the prior art, silicon negative electrode active materials are prepared by breaking silicon by physical force, and when the silicon negative electrode active material is prepared as described above, the grain size is generally greater than 200 nm and the surface is smooth, so that the specific surface area is less than 0.25 m 2 When the silicon-based active material is prepared simply by using the method in the related art, the size of the surface area cannot be controlled, so there is a disadvantage that it is difficult to ensure the service life stability of the negative electrode.

[0181] However, the method for preparing negative electrode active materials according to the present application can form silicon particles by including the following steps: silane gasification is carried out on silicon through a chemical reaction under specific process conditions as described above, and then the silicon-based active material is grown through crystal nucleation; therefore, a silicon-based active material that meets the surface area size and grain size according to the present application can be obtained.

[0182] In addition, when forming a carbon coating on a silicon-based active material according to the present application, a carbon coating can be formed on the surface of the silicon-based active material by heat treatment while flowing a hydrocarbon gas (CO2, methane, ethane, propane, etc.) or an organic solvent (methanol, ethanol, propanol, isopropanol, acetone, etc.) or a combustion gas of a solid carbon material (sawdust, graphite and carbide) together with an inert gas into a continuous reactor in a state where CVD-coated silicon is added.

[0183] In this case, the temperature of the heat treatment may be within a range of 700° C. to 1200° C. inclusive.

[0184] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, the negative electrode for a lithium secondary battery comprising: a negative electrode collector layer; and a negative electrode active material layer comprising the negative electrode composition or a cured product thereof according to the present application formed on one surface or both surfaces of the negative electrode collector layer.

[0185] Figure 1 1 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be confirmed that the negative electrode for a lithium secondary battery 100 includes a negative electrode active material layer 20 on one surface of a negative electrode current collector layer 10. Figure 1 It is shown that the negative electrode active material layer is formed on one surface, but the negative electrode active material layer may be included on both surfaces of the negative electrode collector layer.

[0186] In an exemplary embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry including the negative electrode composition to one surface or both surfaces of the negative electrode collector layer and drying the negative electrode slurry.

[0187] In this case, the negative electrode slurry may include: the negative electrode composition described above; and a slurry solvent.

[0188] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy 5% or more and 40% or less.

[0189] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% or more and 40% or less, preferably 7% or more and 35% or less, and more preferably 10% or more and 30% or less.

[0190] The solid content of the negative electrode slurry may mean the content of the negative electrode composition included in the negative electrode slurry, and may mean the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.

[0191] When the solid content of the negative electrode slurry satisfies the above range, viscosity is suitable during the formation of the negative electrode active material layer, and thus the present invention has a feature of being able to effectively form a negative electrode active material layer by minimizing the particle aggregation phenomenon of the negative electrode composition.

[0192] In an exemplary embodiment of the present application, the slurry solvent may be used without limitation as long as the slurry solvent can dissolve the negative electrode composition, and specifically, water or NMP may be used.

[0193] In an exemplary embodiment of the present application, the negative electrode collector layer generally has a thickness of 1 μm to 100 μm. The negative electrode collector layer is not particularly limited as long as the negative electrode collector layer has high conductivity without causing chemical changes to the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, wherein the surface of copper or stainless steel is treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode collector layer can also enhance the bonding strength of the negative electrode active material by forming fine concave-convex on its surface, and the negative electrode collector layer can be used in various forms, such as a film, a sheet, a foil, a mesh, a porous body, a foam body or a non-woven fabric body.

[0194] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.

[0195] However, the thickness may be variously modified according to the type and purpose of the negative electrode used, and is not limited thereto.

[0196] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.

[0197] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0198] The porosity varies depending on the composition and content of the silicon-based active material, the conductive material, and the binder contained in the negative electrode active material layer, and in particular, by containing the silicon-based active material and the conductive material according to the present application in a specific composition and content so as to satisfy the above-mentioned range, it is characterized in that the conductivity and resistance in the electrode have an appropriate range.

[0199] In an exemplary embodiment of the present application, a lithium secondary battery is provided, the lithium secondary battery including: a positive electrode; the negative electrode for the lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

[0200] Figure 21 is a diagram showing a stacking structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be confirmed that the negative electrode 100 for the lithium secondary battery includes a negative electrode active material layer 20 on one surface of the negative electrode collector layer 10, and it can be confirmed that the positive electrode 200 for the lithium secondary battery includes a positive electrode active material layer 40 on one surface of the positive electrode collector layer 50, and the negative electrode 100 for the lithium secondary battery and the positive electrode 200 for the lithium secondary battery are formed into a structure in which the electrodes are stacked with a separator 30 interposed therebetween.

[0201] A secondary battery according to an exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for a lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described in detail, its specific description will be omitted.

[0202] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.

[0203] In the positive electrode, there is no particular limitation on the positive electrode collector, as long as the positive electrode collector has conductivity without causing chemical changes to the battery, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and the adhesion of the positive electrode active material can also be enhanced by forming fine concavoconvexities on the surface of the collector. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0204] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: a layered compound, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound replaced by one or more transition metals; a lithium iron oxide, such as LiFe3O4; a lithium manganese oxide, such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5 and Cu2V2O7; Ni-site lithium nickel oxide, represented by the chemical formula LiNi 1-c2 M c2O2 (herein, M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and c2 satisfies 0.01≤c2≤0.6); lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3 O2 (here, M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.6) or Li2Mn3MO8 (here, M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4 in which the chemical formula Li is partially replaced by alkaline earth metal ions, etc., but is not limited thereto. The positive electrode may be Li metal.

[0205] In an exemplary embodiment of the present application, the positive electrode active material includes a lithium composite transition metal compound, the lithium composite transition metal compound includes nickel (Ni), cobalt (Co) and manganese (Mn), the lithium composite transition metal compound includes a single particle or a secondary particle, and the single particle may have an average particle size (D50) of 1 μm or more.

[0206] For example, the single particle may have an average particle size (D50) of 1 μm to 12 μm, 1 μm to 8 μm, 1 μm to 6 μm, greater than 1 μm to 12 μm, greater than 1 μm to 8 μm, or greater than 1 μm to 6 μm.

[0207] Even if the single particle is formed into a small particle size with an average particle size (D50) of 1 μm or more and 12 μm or less, the particle strength can be excellent. 2 When the single particle is pressed with a force of 650 kgf / cm 2 The strong calendering of the single particle also reduces the phenomenon of increasing the number of particles in the electrode due to particle breakage, thereby improving the service life characteristics of the battery.

[0208] The single particle may be prepared by mixing a transition metal precursor and a lithium raw material and firing the resulting mixture. The secondary particle may be prepared by a different method from the single particle, and the composition of the secondary particle may be the same as or different from that of the single particle.

[0209] The method of forming the single particles is not particularly limited, but generally, the single particles can be formed by increasing the firing temperature to achieve overfiring, and the single particles can be prepared by using additives such as grain growth promoters that facilitate overfiring or by changing the starting material method.

[0210] For example, the firing is carried out at a temperature capable of forming a single particle. In order to form the single particle, it is necessary to fire at a higher temperature than when preparing the secondary particle. For example, when the composition of the precursor is the same, it is necessary to fire at a temperature of about 30°C to 100°C higher than when preparing the secondary particle. The firing temperature for forming the single particle may vary depending on the metal composition in the precursor. For example, when it is desired to form a high Ni NCM lithium composite transition metal oxide having a nickel (Ni) content of more than 80 mol % as a single particle, the firing temperature may be 700°C to 1000°C, preferably about 800°C to 950°C. When the firing temperature satisfies the above range, a positive active material comprising a single particle having excellent electrochemical properties can be prepared. When the firing temperature is lower than 790°C, a positive active material comprising a lithium composite transition metal compound in the form of a secondary particle can be prepared, and when the firing temperature exceeds 950°C, over-firing may occur, so that a layered crystal structure may not be properly formed, thereby reducing the electrochemical performance.

[0211] In this specification, the single particle is a term used to distinguish a single particle from a secondary particle formed by the aggregation of tens to hundreds of primary particles in the related art, and is a concept that includes a single particle composed of one primary particle and a quasi-single particle that is an aggregate of 30 or less primary particles.

[0212] Specifically, in the present invention, the single particle may be in the form of a single particle composed of one primary particle or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of hundreds of primary particles.

[0213] In an exemplary embodiment of the present application, the lithium composite transition metal compound as the positive electrode active material further includes secondary particles, and an average particle size (D50) of the single particles is smaller than an average particle size (D50) of the secondary particles.

[0214] In the present invention, the single particle may be in the form of a single particle composed of one primary particle, or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.

[0215] The lithium composite transition metal compound may further include secondary particles. The secondary particles refer to a form formed by aggregation of primary particles and can be distinguished from the concept of single particles including one primary particle, one single particle, or a quasi-single particle form that is an aggregation of 30 or less primary particles.

[0216] The secondary particles may have a particle size (D50) of 1 μm to 20 μm, 2 μm to 17 μm, preferably 3 μm to 15 μm. The secondary particles may have a particle size of 0.05 μm 2 / g to 10 m 2 / g, preferably 0.1 m 2 / g to 1 m 2 / g, more preferably 0.3 m 2 / g to 0.8 m 2 / g specific surface area (BET).

[0217] In another exemplary embodiment of the present application, the secondary particles are aggregates of primary particles, and the primary particles have an average particle size (D50) of 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of aggregates of hundreds of primary particles, and the primary particles may have an average particle size (D50) of 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.

[0218] When the average particle size (D50) of the primary particles satisfies the above range, a single-particle positive electrode active material with excellent electrochemical properties can be formed. When the average particle size (D50) of the primary particles is too small, the number of primary particles that form lithium nickel oxide particles increases, thereby reducing the effect of suppressing particle breakage during rolling, and when the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles becomes longer, thereby increasing resistance and output characteristics may deteriorate.

[0219] According to another exemplary embodiment of the present application, the average particle size (D50) of the single particle is characterized by being smaller than the average particle size (D50) of the secondary particle. Therefore, even if the single particle is formed with a small particle size, the single particle can have excellent particle strength, and the excellent particle strength can reduce the phenomenon of an increase in the number of particles in the electrode due to particle rupture, thereby improving the service life characteristics of the battery.

[0220] In an exemplary embodiment of the present application, an average particle diameter (D50) of the single particles is 1 μm to 18 μm smaller than an average particle diameter (D50) of the secondary particles.

[0221] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm, 1.5 μm to 15 μm, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.

[0222] When the average particle size (D50) of the single particle is smaller than the average particle size (D50) of the secondary particle, for example, when the above-mentioned range is met, the single particle can have excellent particle strength even if it is formed with a small particle size. Therefore, the excellent particle strength reduces the phenomenon of an increase in the number of particles in the electrode due to particle breakage, thereby having the effect of improving the service life characteristics of the battery and improving the energy density.

[0223] According to another exemplary embodiment of the present application, based on 100 parts by weight of the positive electrode active material, the content of the single particle is 15 parts by weight to 100 parts by weight. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 20 parts by weight to 100 parts by weight, or 30 parts by weight to 100 parts by weight.

[0224] For example, based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 100 parts by weight or less.

[0225] When the single particle is included within the above range, excellent battery characteristics can be exhibited when combined with the above negative electrode material. In particular, when the amount of the single particle is 15 parts by weight or more, the phenomenon of an increase in the number of particles in the electrode due to particle breakage during the rolling process after manufacturing the electrode can be alleviated, thereby improving the service life characteristics of the battery.

[0226] In an exemplary embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the amount of the secondary particles may be 85 parts by weight or less based on 100 parts by weight of the positive electrode active material. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 0 parts by weight or more.

[0227] When the above range is met, the above effect due to the presence of a single particle of positive electrode active material can be maximized. When a secondary particle of positive electrode active material is included, the composition may be the same as that exemplified in the above single particle positive electrode active material, or may be a different composition, and may be in the form of a single particle aggregate.

[0228] In an exemplary embodiment of the present application, in 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0229] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.

[0230] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation as long as the positive electrode conductive material has electronic conductivity without causing chemical changes to the constituted battery. Specific examples thereof include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used.

[0231] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples thereof may include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.

[0232] The diaphragm separates the negative electrode and the positive electrode, and provides a channel for lithium ion movement, and can be used without particular restriction, as long as the diaphragm is generally used as a diaphragm in a secondary battery, in particular, preferably with excellent electrolyte moisture retention ability and a diaphragm with low resistance to ion movement in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by a polyolefin-based polymer (such as, ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer) or a laminated structure of more than two layers thereof. In addition, a typical porous nonwoven fabric can also be used, for example, a nonwoven fabric made of glass fiber, polyethylene terephthalate fiber, etc. with a high melting point. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.

[0233] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which may be used to prepare lithium secondary batteries, but are not limited thereto.

[0234] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0235] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.

[0236] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonates have a high dielectric constant as high-viscosity organic solvents, thereby dissociating lithium salts well, and therefore can be preferably used. Moreover, since the cyclic carbonates can be mixed with low-viscosity and low-dielectric-constant linear carbonates (such as dimethyl carbonate and diethyl carbonate) in an appropriate ratio to prepare an electrolyte with high conductivity, such cyclic carbonates can be more preferably used.

[0237] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily dissolved in a non-aqueous electrolyte. For example, as the anion of the lithium salt, a metal salt selected from the group consisting of F - , Cl -,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more of the groups consisting of.

[0238] In the electrolyte, in order to improve the service life characteristics of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, on the basis of containing the above-mentioned electrolyte components, one or more additives may be included, for example, halogenated alkylene carbonate compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0239] An exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics and cycle characteristics, and can therefore be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0240] [Mode of invention]

[0241] Hereinafter, preferred embodiments will be proposed to facilitate understanding of the present invention, but the embodiments are provided only for illustrating the present invention, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present invention, and such changes and modifications naturally also fall within the appended claims.

[0242] <Preparation Example>

[0243] <Preparation of Negative Electrode Active Materials in Examples 1 to 6 and Comparative Examples 2 and 3>

[0244] After the chemical reaction, silane gas was deposited on the substrate to form a silicon-based active material. Thereafter, the surface of the silicon-based active material was coated with a carbon coating layer under the conditions shown in Table 1 below.

[0245] <Preparation of Negative Electrode Active Material in Comparative Example 1>

[0246] The negative electrode active material was prepared in the same manner as in Example 1, except that the carbon coating layer in Example 1 was not formed.

[0247]

[0248] <Preparation of negative electrode>

[0249] A negative electrode slurry (solid concentration of 25 wt %) was prepared by adding a negative electrode active material including the silicon-based active material in Table 1, a first conductive material, a second conductive material, and polyacrylamide as a binder at a weight ratio of 80:9.6:0.4:10 to distilled water as a negative electrode slurry forming solvent.

[0250] Specifically, the first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is SWCNT.

[0251] As a specific mixing method, after the first conductive material, the second conductive material, the binder, and water were dispersed at 2500 rpm for 30 minutes using a homomixer, the silicon-based active material was added thereto, and then the resulting mixture was dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.

[0252] 85 mg / 25 cm 2The two surfaces of a copper current collector (thickness: 8 μm) as a negative electrode current collector layer were coated with the negative electrode slurry, and the resulting product was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 33 μm), which was used as a negative electrode (thickness of the negative electrode: 41 μm, porosity of the negative electrode: 40.0%).

[0253] <Manufacturing of Secondary Battery>

[0254] LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black as a conductive material (product name: Super C65, manufacturer: Timcal) and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry in a weight ratio of 97:1.5:1.5 to prepare a positive electrode slurry (solid concentration of 78 wt %).

[0255] At 537 mg / 25 cm 2 The two surfaces of an aluminum current collector (thickness: 12 μm) as a positive electrode current collector were coated with the positive electrode slurry, and the resulting product was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm), thereby preparing a positive electrode (thickness of the positive electrode: 77 μm, porosity 26%).

[0256] A lithium secondary battery was prepared by interposing a polyethylene separator between the positive electrode and each of the negative electrodes of the examples and comparative examples and injecting an electrolyte therein.

[0257] The electrolyte was obtained by adding 3 wt % of vinylene carbonate based on the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) were mixed at a volume ratio of 10:90, and adding LiPF6 as a lithium salt at a concentration of 1 M thereto.

[0258] <Experimental example>

[0259] Experimental Example 1: Evaluation of the service life of a single battery

[0260] The secondary battery containing the negative electrode manufactured in the embodiment and the comparative example was evaluated for service life using an electrochemical charger and discharger, and the capacity retention rate was evaluated. The secondary battery was subjected to an in-situ cycle test at 4.2-3.0 V 1 C / 0.5 C, and the capacity retention rate was measured by charging / discharging the secondary battery at 0.33 C / 0.33 C (4.2-3.0 V) every 50 cycles during the test, and the results are shown in Table 2.

[0261] Life retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the first cycle)}×100

[0262]

[0263] Experimental Example 2: Evaluation of 2.5 C discharge resistance increase rate at SOC50 (after 200 cycles)

[0264] During the test in Experimental Example 1, after measuring the capacity retention rate by charging / discharging the secondary battery at 0.33C / 0.33C (4.2-3.0 V) every 50 cycles, the resistance was measured by discharging the secondary battery at 2.5C pulse at SOC50 to compare and analyze the resistance increase rate.

[0265] Regarding the evaluation of the resistance increase rate, data at 200 cycles were calculated for each test, and the results are shown in Table 3 below.

[0266]

[0267] Experimental Example 3: Evaluation of discharge resistance at SOC50 2.5 C 0.1s in the initial cycle (electrode charge and discharge using a single cell) Resistance measurement)

[0268] The resistance values ​​measured during a predetermined period of time (0.1 s) during 2.5 C pulse discharge were measured using the method used in Experimental Example 2 above, and the results are shown in Table 4 below.

[0269]

[0270] Experimental Example 4: Volume change due to 40°C gas generation during bag testing

[0271] After 20 g of each negative electrode slurry prepared in the examples and comparative examples was put into a bag, the bag was sealed and stored in an oven at 40° C., and then the volume change over time was measured using a measuring cylinder. The results are shown in Table 5 below.

[0272]

[0273] As can be confirmed from the above Tables 2 and 3, it can be confirmed that in the case of Examples 1 to 6 in which the carbon coating layer according to the present application is formed, the service life evaluation and the resistance increase rate are higher than or equal to those in Comparative Examples 1 to 3. This corresponds to the following results: when the silicon-based active material according to the present application is used, the lithium insertion and extraction reaction during charge and discharge can be uniformly reacted, and the stress applied to the silicon-based active material can be reduced to alleviate particle fracture, thereby improving the service life retention rate of the electrode.

[0274] In addition, as can be seen in Tables 4 and 5, in Examples 1 to 6 in which the carbon coating according to the present application was formed, it can be seen that the electrode resistance was formed lower, and it can also be confirmed that the volume change rate was small, compared with Comparative Example 1 in which the carbon coating was not formed.

[0275] In addition, it can be confirmed that in Comparative Examples 2 and 3, when the carbon coating is not carbon having an ID / IG of 0.1 to 1.2 when measured using Raman spectroscopy, but carbon having an ID / IG less than or greater than the corresponding range, as can be seen in Table 4, the discharge resistance increases, and the service life characteristics also deteriorate due to the large volume change rate.

[0276] That is, the present application is characterized in that a carbon coating of specific conditions is formed on at least a portion of the outer surface of the silicon-based active material prepared as described above. Therefore, it can be confirmed that the carbon coating acts as a protective layer, suppresses the reaction between the surface of the silicon-based active material and the solvent during slurry formation, thereby preventing hydrogen generation reaction, and has a feature of being able to reduce uneven electrode coating caused by the generation of bubbles during electrode coating.

[0277] In addition, it can be confirmed that the present application has a feature in that the resistance of the negative electrode active material itself is reduced due to the conductivity of the above-mentioned carbon coating being higher than a predetermined range, and thus the service life stability is improved by reducing the electrode resistance due to the increased conductivity.

Claims

1. A negative electrode active material, comprising: A silicon-based active material; and A carbon coating that surrounds at least a part of the outer surface of the silicon-based active material, wherein when measured using Raman spectroscopy, the carbon coating contains carbon with an ID / IG of 0.1 to 1.2, and the silicon-based active material contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and the content of SiOx (x = 0) is 70 parts by weight or more based on 100 parts by weight of the silicon-based active material.

2. The negative electrode active material according to claim 1, wherein the carbon coating has a thickness of 1 nm or more and 10 μm or less.

3. The negative electrode active material according to claim 1, wherein the silicon-based active material has a grain size of 200 nm or less.

4. The negative electrode active material according to claim 1, wherein the silicon-based active material has an average particle size (D50) of 3 μm to 10 μm.

5. The negative electrode active material according to claim 1, wherein the carbon coating has a conductivity of 100 mS / m or more and 1000 mS / m or less.

6. The negative electrode active material according to claim 1, wherein The arrangement area of the carbon coating is 90% or more based on the outer surface of the silicon-based active material.

7. The negative electrode active material according to claim 1, wherein the carbon coating contains one or more selected from the group consisting of crystalline silicon and amorphous silicon.

8. A method for preparing the negative electrode active material according to any one of claims 1 to 7, the method comprising: Depositing a silicon-based active material onto a substrate by a chemical reaction of a silane gas; Obtaining the silicon-based active material deposited on the substrate; and Forming a carbon coating on at least a part of the outer surface of the silicon-based active material.

9. The method according to claim 8, wherein the silane gas contains one or more gases selected from monosilane, dichlorosilane, and trichlorosilane.

10. The method according to claim 8, wherein the depositing of the silicon-based active material onto the substrate by a chemical reaction of the silane gas is carried out under high-temperature conditions of 100 °C or more.

11. A negative electrode composition, comprising: The negative electrode active material according to any one of claims 1 to 7; A negative electrode conductive material; and A negative electrode binder.

12. The negative electrode composition according to claim 11, wherein Based on 100 parts by weight of the negative electrode composition, the negative electrode active material is present in an amount of 60 parts by weight or more.

13. The negative electrode composition according to claim 11, wherein the negative electrode conductive material comprises a planar conductive material; and a linear conductive material.

14. A negative electrode for a lithium secondary battery, comprising: A negative electrode current collector layer; and A negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer contains the negative electrode composition according to claim 11 or a cured product thereof.

15. The negative electrode according to claim 14, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and The negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.

16. A lithium secondary battery comprising: positive electrode; The negative electrode for a lithium secondary battery according to claim 14; a separator disposed between the positive electrode and the negative electrode; and Electrolytes.

Citation Information

Patent Citations

  • Anode for lithium ion battery

    JP2009080971A

  • Method and device for performing change task, electronic equipment, and readable storage medium

    KR1020220110080A